The Role of Environmental Responsibility and Community Support in Halal Tourism Development - Cynthia Ayu Manggarani; Shine Pintor Siolemba Patiro (Universitas Muhammadiyah Makassar, 2025)
This study investigates the role of environmental responsibility and community support in shaping perceptions of halal tourism through the Social-Ecological Systems (SES) Theory. Using Structural Equation Modeling (SEM) and a survey-based approach, data were collected from 300 respondents across three major halal tourism destinations in Indonesia: Lombok, Aceh, and West Sumatra. The findings reveal that community support significantly influences the perception of halal tourism, highlighting the importance of cultural alignment and local participation in tourism development. Additionally, environmental responsibility positively affects perceptions of halal tourism, suggesting that sustainable practices enhance the sector’s appeal. The study emphasizes that integrating ecological concerns with community engagement fosters a more inclusive and sustainable halal tourism model. These insights contribute to the growing discourse on sustainable tourism, offering practical implications for policymakers and industry stakeholders in designing effective halal tourism strategies. By aligning tourism development with environmental stewardship and local community interests, halal tourism can achieve long-term success while maintaining cultural and ecological sustainability.